Mycetoma in Moshi, Tanzania. (12th January 2021) - Mavura, Daudi; Chapa, Peter; Sabushimike, Doriane; Kini, Lulyritha; Hay, Roderick
Abstract: The geographic spread of the neglected tropical disease mycetoma is still poorly understood, largely because there is no mechanism for official reporting and the general lack of identification facilities in many regions. Nonetheless many countries in the tropics have such cases. This brief report is submitted to provide an example of recent experience of mycetoma in six patients presenting to a single centre in Tanzania.